Cast Blasting Advances and Challenges at Arco's Black Thunder Mine - Robert L. Martin; Brian W. Stump (International Society of Explosives Engineers, 1997)
"The Black Thunder Mine is located in the Powder River Basin of Northeastern Wyoming. Over 39.2million tons of coal were produced at the Black Thunder Mine in 1996. Just over 100 million pounds ofANFO/Emulsion blend were consumed in that same year. Currently around 30% of the overburden is cast to final with the use of explosives. With plans for a mine expansion, explosives will continue to play a very vital roll well into the future."